Evaluating the effects of disciplinary cases among students in colleges of education in Ghana: A case of St Terasa’s College of Education - Dogbe, Mary; Segbefia, Samuel Kwabla; Chireh, Theresa Domobalah (Research Journal in Advanced Social Sciences, 2022)
It is impossible to overstate the value of discipline in human institutions and societies. The achievement of institutional objectives is made possible only through the maintenance of order. Discipline violations in our schools are becoming increasingly common in Ghana. It appears that order is progressively giving way to chaos. Student indiscipline has taken over as the norm in their classrooms. In schools and in the media, horrific incidents such as open confrontations, the destruction of school property and the personal property of students, profanity, drug abuse, examination malpractices, stealing, defiance of school rules and regulations, and other forms of defiance are reported daily. Almost every P.T.A. meeting has had this as the main topic of discussion. It has become a source of concern for many individuals, and everyone is perplexed as to why this is the case. As a result, this study investigated acts of indiscipline committed by students at St. Teresa's College of Education in Hohoe. The study sought to investigate the effects of indiscipline among students of St Teresa’s college education in the Hohoe municipality. An appropriate sample size of first, second, and third-year students, as well as college tutors, was selected from a total population of 469 students and teachers at St. Teresa's College of Education to accomplish this. This study employed a descriptive survey as the research design. The questionnaire was used to elicit responses from students and tutors. The study concluded that maintaining school discipline requires students to follow school rules and regulations once they are made available to them. To avoid indiscipline and student riots, it was suggested that the college administration not only involve students in decision-making, but also obtain consensus with students on allowance deductions.